The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2012
DOI: 10.2169/internalmedicine.51.6376
|View full text |Cite
|
Sign up to set email alerts
|

Successful Management of Cap Polyposis with Eradication of <i>Helicobacter pylori</i> Relapsing 15 Years after Remission on Steroid Therapy

Abstract: A 37-year-old woman was evaluated at our hospital for a treatment-resistant proctosigmoiditis. Fifteen years previously, ulcerative colitis was suspected and she was cured by steroid therapy. Colonoscopy revealed multiple sessile polyps covered with white exudate from the rectum to the sigmoid colon. Histopathological examination revealed a mucosal surface cover of granulation tissue. Based on these findings, cap polyposis was diagnosed. She underwent Helicobacter pylori eradication therapy, and at 1 month aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Some authors hypothesized that its e cacy may be due to other bacteria reacting to the H. pylori eradication therapy or to a systemic immune response caused by sustained H. pylori infection. e intervals from eradication therapy to symptom relief and polyp disappearance were 3 days-1 month and 2-14 months, respectively [10][11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors hypothesized that its e cacy may be due to other bacteria reacting to the H. pylori eradication therapy or to a systemic immune response caused by sustained H. pylori infection. e intervals from eradication therapy to symptom relief and polyp disappearance were 3 days-1 month and 2-14 months, respectively [10][11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…Géhénot et al[ 19 ] suggested the possibility of bacterial infection, reporting on a cap polyposis patient who had no evidence of colonic dysmotility and who was successfully treated with metronidazole. Of the myriad gut microbiota, although H. pylori is not detected in mucosa obtained from cap polyposis lesions[ 10 ], most cases of cap polyposis with H. pylori infection have resolved after H. pylori eradication therapy[ 10 , 11 , 15 , 16 , 18 ]. H. pylori infection is well-known to cause not only gastroduodenal diseases, but also diseases such as idiopathic thrombocytopenic purpura and chronic idiopathic urticaria[ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The patient had no evidence of H. pylori infection by urea breath test, anti- H. pylori antibody, or endoscopic findings ( i.e ., gastric mucosal atrophy or diffuse redness of gastric mucosa). However, according to previous evidence that H. pylori eradication therapy was effective for patients with cap polyposis[ 10 , 11 , 15 , 16 ], H. pylori eradication therapy with vonoprazan 20 mg, amoxicillin 750 mg and clarithromycin 200 mg twice daily for 7 d was initiated. Abdominal symptoms ( i.e ., hematochezia and tenesmus), bowel habits, and endoscopic findings did not improve over the six months after therapy.…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…Conservative treatment modalities like avoidance of straining at defecation, use of metronidazole, infliximab, Helicobacter pylori eradication therapy and endoscopic polypectomy have been shown to be beneficial in some cases. [1314] Surgical resection should be reserved for patients with recurrence or for those who don’t respond to conservative therapy. To conclude, rectal CP should be considered in the differential diagnosis of patients presenting clinically with intermittent rectal bleeding and rectal polyposis on endoscopic examination.…”
Section: Discussionmentioning
confidence: 99%